Establishing a national biosafety and biosecurity agency for the United States - Gillum, David R.; Moritz, Rebecca; Koblentz, Gregory D. (Frontiers in Bioengineering and Biotechnology, 2024)
The rapid advancement of biological research and biotechnology requires a novel and robust regulatory agency to ensure uniform biosafety and biosecurity governance in the United States. The current fragmented regulatory landscape needs to be refocused to address the complexities of modern biological research, including risks associated with accidental, inadvertent, and deliberate biological incidents. An independent government agency, which we call the National Biosafety and Biosecurity Agency (NBBA), that is devoted to biosafety and biosecurity could effectively address these challenges. The NBBA would consolidate various regulatory functions, streamline processes, and enhance oversight. This oversight would encompass life sciences research in the United States, regardless of the source of funding or level of classification. The agency could also contribute to the bioeconomy by streamlining requirements to safeguard public health and the environment while fostering scientific and commercial progress. The proposed agency would govern highrisk biological pathogens, manage the Federal Select Agent Program, enforce policies related to dual use research of concern, pathogens with enhanced pandemic potential, and nucleic acid synthesis screening, administer regulations on the use and care of laboratory animals, as well as regulate other relevant biosafety and biosecurity activities. The goal would be to provide one-stop shopping for the biomedical research and biotechnology sectors subject to oversight by the Federal government. To ensure leadership in global biosafety and biosecurity, the agency's mission would include international collaboration, applied research, education, workforce development, and coordination with national security initiatives. Creating an agency like the NBBA will be politically challenging but presenting a comprehensive vision and engaging stakeholders early and frequently, and being transparent in the process, will be essential for garnering support. Creating a unified biosafety and biosecurity governance system in the United States will ensure the safe and secure advancement of biological research while sustaining innovation and maintaining international competitiveness.